Protection of trafficked victims: a comparative study between Malaysia and the United States of America / Clinton Sigau Anyi...[et al.] - Anyi, Clinton Sigau; Noorizan, Muhamad Ariff; Amran, Ammar Iyyad; Noor Azam, Muhamad Nur Aizat (Faculty of Law, 2013)
This research is regarding the protection provided to the victims of human right trafficking. The law which we are focusing in this research is the law provided in Malaysia, anti-Trafficking in Persons and Anti-Smuggling of Migrants Act 2007 (ATIPSOM). Comparison was made with law in United States of America which is Victims of Trafficking and Violence Protection Act (TVPA) 2000. In this research too, the scenario of human trafficking in ASEAN region are also being highlighted. Various countries around ASEAN are being discussed by providing an overview of human trafficking activities in each countries. Each country are being classified in different tier according to their efforts in combating the issue of human rights based on the Trafficking in Person (TIP) Report.This research focus on various types of protections which are being proteeted by the law in both countries in term of shelters, medical assistance, civil remedies and also legal assistance. Comparison were made in order to identify the lacunae in Malaysian law and highlight the strength of the law which are being provided in United States